Accurate quantitation of JAK2 V617F allele burden by array‐based digital PCR. (25th June 2014) - Kinz, E.; Leiherer, A.; Lang, A. H.; Drexel, H.; Muendlein, A.
Summary Introduction The JAK2 V617F mutation is highly prevalent in patients with myeloproliferative neoplasms (MPN). Several studies have shown that allele burden correlates with hematologic characteristics and clinical end‐points in patients with MPN. Allele‐specific real‐time quantitative polymerase chain reaction (RQ‐PCR) is probably the most commonly used technique for detection and quantitation of the JAK2 V617F mutation. Alternatively, digital PCR is an emerging technology for absolute DNA quantitation, which is based on dilution and high‐grade partitioning of a sample. Methods We compared array‐based digital PCR using the QuantStudio™ 3D Digital PCR System platform with a RQ‐PCR assay, CE‐registered for in vitro diagnostic use, regarding JAK2 V617F allele quantitation. This study included 30 samples positive for the JAK2 V617F mutation and additionally 13 samples without the mutation. Results JAK2 V617F allele burden of samples ranged between well below 1% and more than 90%. Linear regression analysis showed a high correlation between the results obtained from the two techniques (r2 = 0.9983). Thirteen samples tested negatively for the JAK2 V617F mutation with RQ‐PCR were also found negative with digital PCR. Conclusion We conclude that array‐based digital PCR is an appropriate method for the quantitation of JAK2 V617F allele burden demonstrating highest correlation with allele‐specific RQ‐PCR.